The Role of Entrepreneurial Culture in Improving the Performance of Micro, Small and Medium Enterprises in Yogyakarta - Fasiha, Fasiha; Erwin, Erwin; Musdalifah, Uci (Hasanuddin Economics and Business Review, 2024)
This research aims to explore the influence of entrepreneurial culture on the performance of micro, small and medium enterprises (MSMEs. This research uses quantitative research. The population in this research is MSME actors in Yogyakarta. Sampling uses purposive sampling, resulting that the sample for this research is 101. The data is analyzed using analysis regression. The results of this research show that entrepreneurial culture has an influence on business performance. The results of this research contribute to business actors paying attention to entrepreneurial culture in order to improve business performance. In addition, this research from a theoretical aspect becomes an additional reference regarding the relationship between entrepreneurial culture and performance business for MSMEs